Chromatin landscape instructs precise transcription factor regulome during embryonic lineage specification - Liping Wang; Shanru Yi; Xinyu Cui; Zhenxiang Guo; Mengting Wang; Xiaochen Kou; Yanhong Zhao; Hong Wang; Cizhong Jiang; Shaorong Gao; Guang Yang; Jiayu Chen; et al. (Cell Reports, 2024)
Summary: Embryos, originating from fertilized eggs, undergo continuous cell division and differentiation, accompanied by dramatic changes in transcription, translation, and metabolism. Chromatin regulators, including transcription factors (TFs), play indispensable roles in regulating these processes. Recently, the trophoblast regulator TFAP2C was identified as crucial in initiating early cell fate decisions. However, Tfap2c transcripts persist in both the inner cell mass and trophectoderm of blastocysts, prompting inquiry into Tfap2c’s function in post-lineage establishment. In this study, we delineate the dynamics of TFAP2C during the mouse peri-implantation stage and elucidate its collaboration with the key lineage regulators CDX2 and NANOG. Importantly, we propose that de novo formation of H3K9me3 in the extraembryonic ectoderm during implantation antagonizes TFAP2C binding to crucial developmental genes, thereby maintaining its lineage identity. Together, these results highlight the plasticity of the chromatin environment in designating the genomic binding of highly adaptable lineage-specific TFs and regulating embryonic cell fates.